3D game textures : create professional game art using Photoshop - Ahearn, Luke (Online access with DDA: Askews (Maths), 2016)
Luke Ahearn teaches all you need to know about texturing game worlds, with the tricks and tools of the trade. He begins with the instructions you will likely be given on the job, walks you through the research and planning phase and moves onto the process of building textures for the scene at hand.